Вплив процесів глобалізації на розвиток соціальної думки Української Православної Церкви - Мартишин, Денис Сергійович (My University, 2018)
Подано виклад сучасних теоретичних засад соціального вчення Православної Церкви в Україні. Показано взаємозв’язок соціальної доктрини Церкви з культурними, політичними, економічними, національними змінами у житті України. Спираючись на соціальне вчення Православної Церкви, розкрито основні поняття й напрями соціальної думки християнства. Розглянуто особливості розвитку Української Православної Церкви, шляхи взаємовідносин Церкви та суспільства в умовах глобалізації, обґрунтовано, що Українська Православна Церква була, є і буде невід’ємною частиною української культури, історії та майбутнього глобального світу. Діалог Церкви та суспільства постійно буде базисним елементом суспільного розвитку та платформою справжніх процесів демократизації в Україні. The article presents a presentation of the modern theoretical foundations of the social teaching of the Orthodox Church in Ukraine. The relationship between the social doctrine of the Church and cultural, political, economic, and national changes in the life of Ukraine is shown. Based on the social teaching of the Orthodox Church, the main concepts and directions of social thought of Christianity are revealed. The peculiarities of the development of the Ukrainian Orthodox Church, the ways of the relationship between the Church and society in the conditions of globalization are considered, it is substantiated that the Ukrainian Orthodox Church was, is, and will be an integral part of Ukrainian culture, history, and the future of the global world. The dialogue between the Church and society will always be a basic element of social development and a platform for genuine democratization processes in Ukraine.
Keywords: глобалізація; globalization; соціальна думка; social opinion; Ukrainian Orthodox Church; Ukrainian Orthodox Church